Toxicity Evaluation of a Novel Magnetic Resonance Imaging Marker, CoCl2-N-Acetylcysteine, in Rats - Li Wang; Mihai Gagea; Karen Martirosyan; Mary Johansen; Timothy Madden; Lisa Norberg; Kirk S. Culotta; Steven J. Frank (Journal of Toxicology)
C4 (cobalt dichloride-N-acetylcysteine [1% CoCl2:2% NAC]) is a novel magnetic resonance imaging contrast marker that facilitates visualization of implanted radioactive seeds in cancer brachytherapy. We evaluated the toxicity of C4. Rats were assigned to control (0% CoCl2:NAC), low-dose (0.1% CoCl2:2% NAC), reference-dose (C4), and high-dose (10% CoCl2:2% NAC) groups. Agent was injected into the left quadriceps femoris muscle of the rats. Endpoints were organ and body weights, hematology, and serum chemistry and histopathologic changes of tissues at 48 hours and 28 and 63 days after dosing. Student’s t tests were used. No abnormalities in clinical signs, terminal body and organ weights, or hematologic and serum chemistry were noted, and no gross or histopathologic lesions of systemic tissue toxicity were found in any treatment group at any time point studied. At the site of injection, concentration-dependent acute responses were observed in all treatment groups at 48 hours after dosing and were recovered by 28 days. No myofiber degeneration or necrosis was observed at 28 or 63 days in any group. In conclusion, a single intramuscular dose of C4 produced no acute or chronic systemic toxicity or inflammation in rats, suggesting that C4 may be toxicologically safe for clinical use in cancer brachytherapy.